2017
DOI: 10.1093/biolre/iox132
|View full text |Cite
|
Sign up to set email alerts
|

Lesion development is modulated by the natural estrous cycle and mouse strain in a minimally invasive model of endometriosis†

Abstract: Many rodent models of endometriosis are invasive, involving surgery to implant donor endometrial tissue into recipient animals. Moreover, few studies have compared and contrasted lesions between rodent strains and estrous stages without exogenous hormone manipulation. This is despite extensive data demonstrating that genetic and hormonal factors can influence endometriosis progression. Here, we have refined a minimally invasive model of endometriosis using naturally cycling mice (donor and recipient matched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 58 publications
7
36
1
Order By: Relevance
“…To clarify the role of IL-1 in lesion formation, we used C57BL/6-background IL-1R1-deficient mice for the endometriosis model. As previously reported, C57BL/6 mice exhibited smaller lesion formation than BALB/c mice (38). In Il1r1 −/− mice, only very small lesions were observed compared with WT mice (Figure 3C).…”
Section: Resultssupporting
confidence: 86%
“…To clarify the role of IL-1 in lesion formation, we used C57BL/6-background IL-1R1-deficient mice for the endometriosis model. As previously reported, C57BL/6 mice exhibited smaller lesion formation than BALB/c mice (38). In Il1r1 −/− mice, only very small lesions were observed compared with WT mice (Figure 3C).…”
Section: Resultssupporting
confidence: 86%
“…In accordance with Dodds et al, lesions were most often observed on the stomach and pancreas, although lesions could also be retrieved from other parts of the abdominal cavity (i.e., gonadal adipose tissue and intestines) [28]. The presence of adhered endometriosis lesions on the peritoneum or subcutaneously is most likely due to residual tissue fragments that were on the tip of the catheter when withdrawing the instrument from the abdominal cavity [28]. The proliferation of the endometriosis lesions was left under the control of the natural estrus cycle of the recipient animals.…”
Section: Discussionsupporting
confidence: 84%
“…This parameter was approximately 2 mg/g body weight in the mouse model [9], compared to 1.5 mg/g body weight in the rat endometriosis model. In accordance with Dodds et al, lesions were most often observed on the stomach and pancreas, although lesions could also be retrieved from other parts of the abdominal cavity (i.e., gonadal adipose tissue and intestines) [28]. The presence of adhered endometriosis lesions on the peritoneum or subcutaneously is most likely due to residual tissue fragments that were on the tip of the catheter when withdrawing the instrument from the abdominal cavity [28].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…To induce endometriosis-like lesions in mice, we employed a method previously developed by our laboratory. 31 This particular model was favored as it avoids surgery and exogenous hormone administration, which in themselves can alter glial reactivity [32][33][34] and therefore could confound results. Donor animals (n ¼ 5) were sacrificed by cervical dislocation while under deep inhaled isoflurane anesthesia.…”
Section: Induction Of the Minimally Invasive Mouse Model Of Endometriosismentioning
confidence: 99%